Conceptualising consumer-based service brand equity (CBSBE) and direct service experience in the airline sector - Sarker, Md Moniruzzaman; Mohd-Any, Amrul Asraf; Kamarulzaman, Yusniza (Elsevier, 2019)
The intense competition taking place in the airline sector requires a concurrently suitable branding strategy. Although contemporary brand equity models have been acknowledged and tested in the service branding context, they are not quite adaptable to the airline sector. These models are more appropriate for product-dominant brands, as they ignore the crucial roles of direct service experience and brand consistency in creating airline brand equity. Therefore, through a systematic and critical review of the literature, we propose a conceptualisation of consumer-based service brand equity (CBSBE) model by emphasising the importance of direct service experience and brand consistency that will equip airline marketing/brand managers to design effective branding strategies.